2011
DOI: 10.1007/s12010-011-9194-2
|View full text |Cite
|
Sign up to set email alerts
|

Onsite Enzyme Production During Bioethanol Production from Biomass: Screening for Suitable Fungal Strains

Abstract: Cellulosic ethanol production from biomass raw materials involves process steps such as pre-treatment, enzymatic hydrolysis, fermentation, and distillation. Use of streams within cellulosic ethanol production was explored for onsite enzyme production as part of a biorefinery concept. Sixty-four fungal isolates were in plate assays screened for lignocellulolytic activities to discover the most suitable fungal strain with efficient hydrolytic enzymes for lignocellulose conversion. Twenty-five were selected for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…This can be reduced by using a local on-site production, which decentralizes the process, making it overall more economically feasible [3]. The composition of the enzymatic blends for hydrolysis is shown to be dependent on the growth substrate [4,5]. It is therefore rational to produce on-site enzymatic blends, using the specific pretreated feedstock, which in turn will be enzymatically hydrolyzed by this enzymatic cocktail.…”
Section: Introductionmentioning
confidence: 99%
“…This can be reduced by using a local on-site production, which decentralizes the process, making it overall more economically feasible [3]. The composition of the enzymatic blends for hydrolysis is shown to be dependent on the growth substrate [4,5]. It is therefore rational to produce on-site enzymatic blends, using the specific pretreated feedstock, which in turn will be enzymatically hydrolyzed by this enzymatic cocktail.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the viable bioconversion of biomass requires not only that the cost of the enzymes be reduced, but also that improvements be made in the effectiveness of the enzymatic extracts used in the hydrolysis mixture. These aspects are highly dependent on both the raw material and the pretreatment employed (Delabona et al, 2012a;Jorgensen and Olsson, 2006;Sorensen et al, 2011;Sukumaran et al, 2009). On-site production of enzymes can help to reduce enzyme costs since there is less need to stabilize the enzyme preparations, avoiding costs associated with transport and storage for long periods.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of the same lignocellulosic biomass for enzyme production and hydrolysis could reduce the production costs of bioethanol, since both process could be co-located and share infrastructure and utilities (Delabona et al, 2012a). The on-site enzyme production using a split stream from the bioethanol process as part of the fermentation medium could be an attractive alternative (Kovacs et al, 2009;Sorensen et al, 2011). Moreover, the production of enzymes using as carbon source the same lignocellulosic material that will be used in the hydrolysis has shown that these enzyme preparations can present better performance (Delabona et al, 2012a;Jorgensen and Olsson, 2006 Efficient degradation of cellulose requires the cooperation of at least three types of enzymes: cellobiohydrolases, endoglucanases, and b-glucosidases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, on-site enzyme production has other advantages over external production, such as the possibility of using a fraction of the sugarcane juice or hydrolysate as sugar source, the production of a less purified enzyme mixture since there would be no need to transport it over long distances and potential to decrease costs, since purchasing commercial enzymes is a great economical constraint against second-generation ethanol feasibility (Sørensen et al 2011).…”
Section: Economic Aspects Of First-and Second-generation Ethanol Prodmentioning
confidence: 99%